2009
DOI: 10.1111/j.1574-695x.2008.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of small Rho GTPases and actin ring formation in epithelial cells during the invasion byCandida albicans

Abstract: Invasion of epithelial cells is a major virulence determinant of Candida albicans; however, the molecular events that occur during invasion are not discerned. This study is aimed to elucidate the role of the host's actin remodeling and involvement of small GTPases during invasion. Actin filaments formed a rigid ring-like structure in the rabbit corneal epithelial cell line SIRC after C. albicans invasion. During invasion, an increase in the mRNA content of Cdc42, Rac1 and RhoA GTPase was observed in SIRC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…5B, inhibition of Rac1 significantly decreased the percent relative R. montanensis invasion of tick cells compared to that in the untreated control by 38% (P Ͻ 0.0001) at a 1 mM concentration of the inhibitor used. Consistently with the suggested role of Rac in R. parkeri, L. monocytogenes, and Candida albicans invasion of mammalian and Drosophila cells (9,43,53), Rac1 inhibition correlates with R. montanensis infection in tick cells. In contrast, experiments employing dominant negative Rac1 mutants suggested that Rac was not involved in R. conorii invasion of Vero cells (6).…”
Section: Fig 3 Arp2/3 Complex Is Important For Rickettsial Internalizsupporting
confidence: 52%
“…5B, inhibition of Rac1 significantly decreased the percent relative R. montanensis invasion of tick cells compared to that in the untreated control by 38% (P Ͻ 0.0001) at a 1 mM concentration of the inhibitor used. Consistently with the suggested role of Rac in R. parkeri, L. monocytogenes, and Candida albicans invasion of mammalian and Drosophila cells (9,43,53), Rac1 inhibition correlates with R. montanensis infection in tick cells. In contrast, experiments employing dominant negative Rac1 mutants suggested that Rac was not involved in R. conorii invasion of Vero cells (6).…”
Section: Fig 3 Arp2/3 Complex Is Important For Rickettsial Internalizsupporting
confidence: 52%
“…In C. albicans , small GTPases such as Cdc42 and Ras1 have been extensively investigated for their roles in regulating hyphal growth and tissue invasion111220212223. To unravel novel gene functions, we have constructed a haploid gene-deletion library covering mostly genes encoding uncharacterized GTPases and their regulators listed in the Candida Genome database (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Chlamydia trachomatis requires solely Rac for internalization [30]. In other cases, a combination of two GTPases allows invasion, as in the case of Candida albicans that needs Rho and Rac to modulate actin cytoskeleton organization [31]. Specific inhibitors and expression of dominant-negative derivatives demonstrated that the Rck-mediated entry process was dependent on the mobilization of actin microfilaments that were activated by the signaling Arp2/3 complex and the GTPases Rac and Cdc42, but not by Rho.…”
Section: Discussionmentioning
confidence: 99%